Pengaruh Kombinasi Media Tanam Dan Dosis Pupuk Npk Terhadap Pertumbuhan Tanaman Tubo Bala (globba leucantha var. Bicolor holttum) - Nurcahyo Widyodaru; Muharik Fauzan; Wagiono; Slamet Abadi (Faculty of Agriculture University of Singaperbangsa Karawang, 2022)
Research is conducted in Dayeuhluhur Subdistrict, Cilacap County, Central Java from September to in November 2020. The study aims to gain the best influence of planting medi and fertilizer dose of compound NPK of tubo bala plant (Globba leucantha var. bicolor Holttum). The research method using the experimental method of Rancangan Acak Kelompok (RAK) there are 12 treatments repeated five times and consisting of 60 experimental units. The observed parameters namely the beginnings appear flowers, the beginnings of bloom flowers, the presentages of flower formation, the presentases of blooming flowers, the amount of fruit and the number of bulbils. The results of the study showed in treatment I (Tanah:pasir:bokashi (1:1:1) + NPK 0 gram) giving the best result in early mumculnya of 25th day interest after planting, early blooming flower of 36th day after planting, presentation of benign interest of 80%, presentage of blooming interest of 72.22%, fruit amount of 4 fruits and number of bulbils of 13 bulbils.